2020
DOI: 10.3390/jcm9040980
|View full text |Cite
|
Sign up to set email alerts
|

Fully Digital Workflow for Planning Static Guided Implant Surgery: A Prospective Accuracy Study

Abstract: The accuracy of static guided implant surgery (sGIS) using conventional planning workflow has been extensively examined; however, more information is required to justify the application of fully digital planning protocol. The purpose of this study was to investigate the clinical accuracy of sGIS with a fully digital planning workflow. Twenty-one partially edentulous patients were enrolled in this prospective study. Cone-beam computed tomography (CBCT) and intraoral scans were taken and superimposed by matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…A systematic review of 24 clinical and preclinical studies by Tahmaseb et al [ 21 ] revealed mean total errors of 1.12 mm at the implant platform and 1.39 mm at the implant apex, and a mean angular deviation of 3.89°. The mean error in our study was 0.44 mm at the entry point (implant platform) for FDW and 0.85 for PDW, similar to the results obtained by Lin et al [ 34 ] (0.78 mm), Cristache and Gurbanescu 0.79 mm [ 4 ] and Kiatkroekkrai et al 0.87(full digital group) and 1.01 (partially digital group) [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review of 24 clinical and preclinical studies by Tahmaseb et al [ 21 ] revealed mean total errors of 1.12 mm at the implant platform and 1.39 mm at the implant apex, and a mean angular deviation of 3.89°. The mean error in our study was 0.44 mm at the entry point (implant platform) for FDW and 0.85 for PDW, similar to the results obtained by Lin et al [ 34 ] (0.78 mm), Cristache and Gurbanescu 0.79 mm [ 4 ] and Kiatkroekkrai et al 0.87(full digital group) and 1.01 (partially digital group) [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, operators should be aware of the errors that inevitably occur because of the morphological differences between matched images, and they should focus on minimizing additional operator errors caused by inappropriate manual works. In this study, point-based surface registration was performed in planning software programs that are widely used in guided implant surgery [9]. The general results were similar in the 2 software programs.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, point-based surface registration was performed in planning software programs that are widely used in guided implant surgery [ 9 ]. The general results were similar in the 2 software programs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations